If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + 15 = 6x + 7 Reorder the terms: 15 + 10x = 6x + 7 Reorder the terms: 15 + 10x = 7 + 6x Solving 15 + 10x = 7 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 15 + 10x + -6x = 7 + 6x + -6x Combine like terms: 10x + -6x = 4x 15 + 4x = 7 + 6x + -6x Combine like terms: 6x + -6x = 0 15 + 4x = 7 + 0 15 + 4x = 7 Add '-15' to each side of the equation. 15 + -15 + 4x = 7 + -15 Combine like terms: 15 + -15 = 0 0 + 4x = 7 + -15 4x = 7 + -15 Combine like terms: 7 + -15 = -8 4x = -8 Divide each side by '4'. x = -2 Simplifying x = -2
| x/2+x/8=8 | | 5(y-6)=7y-30 | | 6(n-5)=66 | | -5x-6+9=-19 | | x=4(90-x)+5 | | 127-r=62 | | -3(4X-3)=-12x+13 | | -5x-6+9=19 | | 0=8/12y-40 | | 7x-2=(x+1) | | -2x-8+6=7-4x-x | | -1(h+13)=5 | | 49-5=2a-3 | | 2(x-2)=-5 | | 2+4+3x=18 | | 14-(2c+5)=-7c+29 | | 5(2x-3)-x+8=13 | | 33=528x | | 10x+10 = +9x+15 | | X+4=-2-5x | | -2(x-4)=22 | | 7+4(7+4-25)= | | 4h+1+12h=36 | | 3x+57=7x+9 | | -(8y+1)-(-7y-3)=2 | | 15-29=2(x-3) | | 7+s^2(t+4-5r)= | | 5a+8+(-2)=-7 | | -(8y+1)-(-7y-3)=3 | | -(6y+4)-(-5y-6)=5 | | 100(z+3)-3(z-1)=4(z-3)+(z-1) | | y=2(-3) |